Comparative study of verdicts of poison in Islamic jurisprudence Sentences, Poison, , Islamic religions, Poisoning - Farzad Parsa; Sajed Adak (Zanco Journal of Humanity Sciences)
Poison is a harmful and harmful substance for the living tissues of the body and a biological system, and in many cases, such as murder, insect repellency, and treatments, these can be used, Therefore, Sam has been the subject of various jurisprudence such as commerce, hunting, jihad, qisas and among them. The citation and inference areas of the jurists in these discussions are in general the attention to the harm caused by the poison, the rules such as "Lazar" and some related verses and narrations, and the necessities and requirements and conditions of life of individuals and the Islamic community. The similarity of the citation grounds has led to the closeness and closeness of the ulama's view to most of the sentences and is often considered to be toxic due to the harmfulness of impure and incomprehensible And prohibiting haram, and do not consider it worthwhile to trade with it for the sake of non-profit or harmful, forbidden, and non-taxable. And the therapeutic use of it has, like other restrictions, been made necessary. They have considered the poison as deadly and kill the poison caused by other conditions, deliberately. The jurists are taking revenge against the poison due to the forbiddenness of this article and the attention of some hadiths about the need for retaliation with the "sword" and Observance of Ehsan in killing and the fear of some unwanted conditions because of the failure to observe the right of Allah to swallow Ghusl and the spread of poison to the bathers do not. The jurists also frequently prescribed the use of poison against pagans and during jihad, but some of them have been denied or restricted to necessity.